PENERAPAN METODE SAVING MATRIX DALAM PENENTUAN RUTE TERPENDEK PENGANGKUTAN SAMPAH DI KABUPATEN KUBU RAYA - Ikbal Muhaimin; Yundari Yundari; Meliana Pasaribu (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
The process of transporting waste from the Waste Disposal Site (TPS) to the Final Disposal Site (TPA) is one of the problems in Kubu Raya district that needs attention. This is because the volume of waste in each TPS in Kubu Raya varies, and the number and capacity of transport vehicles provided by the PUPR Office of Kubu Raya is limited. Of course, these problems affect the distance traveled by the transport vehicle, travel time and costs incurred. Therefore, it is necessary to choose the optimal transportation route. The route is said to be optimal when each TPS is transported one way and does not exceed the capacity of the conveyance, so that the total distance obtained is the minimum total distance. The existing problems are then modeled in mathematical form and solved using the Saving Matrix method. This method combines destination points that can be traversed one way by paying attention to the volume of demand for each destination so as not to exceed the vehicle capacity. Based on the research results obtained four optimal vehicle routes with a total distance of 141.6 km. with details for the distance of vehicle route one which is 41.5 km, vehicle route two is 35.95 km, vehicle route three is 35.9 km, and vehicle route four is 28.25 km. This shows that the application of the Saving Matrix method provides more efficient results compared to the previous route of 162 km